2010
DOI: 10.1074/jbc.m110.116988
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Induces ERK-dependent Formation of a Phospho-c-Fos·c-Jun Activator Protein-1 Complex That Causes Apoptosis in Macrophages

Abstract: Macrophages are essential components of innate immunity, and apoptosis of these cells impairs mucosal defense to microbes. Helicobacter pylori is a gastric pathogen that infects half of the world population and causes peptic ulcer disease and gastric cancer. The host inflammatory response fails to eradicate the organism. We have reported that H. pylori induces apoptosis of macrophages by generation of polyamines from ornithine decarboxylase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 60 publications
(105 reference statements)
4
83
0
Order By: Relevance
“…+ myeloid cells and CD11b -nonmyeloid cells from the gastric lamina propria of mice infected with H. pylori premouse Sydney strain 1 (PMSS1) for 48 h, the peak of gastric macrophage infiltration (6,41) Fig. S2 C-E).…”
Section: Myeloid-specific Odc Deletion Enhances Gastritis and Bacterimentioning
confidence: 99%
See 2 more Smart Citations
“…+ myeloid cells and CD11b -nonmyeloid cells from the gastric lamina propria of mice infected with H. pylori premouse Sydney strain 1 (PMSS1) for 48 h, the peak of gastric macrophage infiltration (6,41) Fig. S2 C-E).…”
Section: Myeloid-specific Odc Deletion Enhances Gastritis and Bacterimentioning
confidence: 99%
“…Importantly, polyamines have also been implicated in the alteration of histone modifications and chromatin structure and thus might broadly affect DNA stability and transcription (3)(4)(5). The production of the three major polyamines-putrescine, spermidine, and spermine-is tightly regulated and centers on the rate-limiting enzyme, ornithine decarboxylase (ODC1, hereafter referred to as ODC) (2,6). ODC uses the substrate, L-ornithine, to produce putrescine via a decarboxylation reaction (2,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Helicobacter pylori has been reported to activate MAPK3 enzymes (Asim et al, 2010). When invading the human-derived monocyte cell line THP-1, H. pylori-stimulates the extression of IL-18 that was reduced by either ERK or p38 inhibitors (Yamauchi et al, 2008).…”
Section: Disruption Of Mapk Signalling Pathwaysmentioning
confidence: 99%
“…A study by Nozawa et al (2002) indicated that the stimulation of the ERK signalling pathway by H. pylori may be directly responsible for NFkB activation and subsequent synthesis of IL-8. Moreover, when phosphorylated, ERK (pERK) translocates to the nucleus, which can result in the activation of other transcription factors, including activator protein-1, which when bound to the IL-8 promoter region would lead to maximal gene expression (Asim et al, 2010;Hoffmann et al, 2002). The role of CagA in ERK activation has been studied previously (Zhao et al, 2010).…”
Section: Mechanism Of Inflammation Gastric Inflammation In Hmentioning
confidence: 99%